PENGARUH RENCANA PENINGKATAN VOLUME TAMPUNGAN TERHADAP STABILITAS TUBUH BENDUNGAN KEDUNG OMBO - Gerald Guntur Pandapotan Siregar (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2023)
The strategy to meet the water demands of Semarang and Demak Regencies involves enhancing the storage capacity of the Kedung Ombo Dam. This augmentation will inevitably alter the typical water level, thereby affecting the stability of the dam structure as it bears a greater load. Furthermore, the Kedung Ombo Dam, which is nearly 32 years old, necessitates re-evaluation since it lacks the full benefit of contemporary design methods. This study is confined to examining the slope stability, both static and pseudostatic, at a steady state flow, with the highest normal water level elevation (elevation +92.00) as the focal point. The slope stability analysis was conducted via the finite element method using the Slope/W in Geo-Studio software. The outcome of the static slope stability analysis indicates that the safety factor of the Kedung Ombo Dam body remains above the minimum allowable safety factor. In the pseudostatic analysis, the safety factor during the Operating Basic Earthquake (OBE) remains above the minimum allowable safety factor. However, during the Maximum Design Earthquake (MDE), the safety factor demonstrates a value that is lower than the minimum allowable safety factor. Nevertheless, the analysis of fixed displacement or permanent deformation reveals that the maximum settlement that occurs during the MDE earthquake does not exceed 50% of the available freeboard.